2020
DOI: 10.1111/jnc.15109
|View full text |Cite
|
Sign up to set email alerts
|

Study of the release of endogenous amines in Drosophila brain in vivo in response to stimuli linked to aversive olfactory conditioning

Abstract: A highly challenging question in neuroscience is to understand how aminergic neural circuits contribute to the planning and execution of behaviors, including the generation of olfactory memories. In this regard, electrophysiological techniques like Local Field Potential or imaging methods have been used to answer questions relevant to cell and circuit physiology in different animal models, such as the fly Drosophila melanogaster. However, these techniques do not provide information on the neurochemical identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
(140 reference statements)
0
5
0
Order By: Relevance
“…[7] Also, behaviorally evoked serotonin responses in the Drosophila MB calyx were delayed from the presentation of an odorant stimulant. [15] The delay could be caused by dopamine being indirectly activated by multiple modulatory pathways. Imaging and genetic studies revealed that octopamine triggers dopamine activity for sugar reward to form appetitive memory by regulating dopaminergic neurons in the MB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Also, behaviorally evoked serotonin responses in the Drosophila MB calyx were delayed from the presentation of an odorant stimulant. [15] The delay could be caused by dopamine being indirectly activated by multiple modulatory pathways. Imaging and genetic studies revealed that octopamine triggers dopamine activity for sugar reward to form appetitive memory by regulating dopaminergic neurons in the MB.…”
Section: Methodsmentioning
confidence: 99%
“…A similar phenomenon was observed in behavior studies in rats, where phasic dopamine changes were measured a few seconds after an unpredicted food reward (sugar pellet) was delivered [7] . Also, behaviorally evoked serotonin responses in the Drosophila MB calyx were delayed from the presentation of an odorant stimulant [15] . The delay could be caused by dopamine being indirectly activated by multiple modulatory pathways.…”
Section: Figurementioning
confidence: 99%
“…[7] Also, behaviorally evoked serotonin responses in the Drosophila MB calyx were delayed from the presentation of an odorant stimulant. [15] The delay could be caused by dopamine being indirectly activated by multiple modulatory pathways. Imaging and genetic studies revealed that octopamine triggers dopamine activity for sugar reward to form appetitive memory by regulating dopaminergic neurons in the MB.…”
Section: Methodsmentioning
confidence: 99%
“…Fast‐scan cyclic voltammetry (FSCV) is an electrochemical technique that measures sub‐second concentration changes and provides fingerprint cyclic voltammograms to identify neurochemicals [12] . FSCV has been previously employed to measure neuromodulators in Drosophila larval ventral nerve cord (VNC) and in the adult central complex and MB [13–15] . Moreover, a similar approach was implemented to measure dopamine in the honey bee [16] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation